2020
DOI: 10.1039/c9bm01005j
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic loads distinctively impact the secretory profile of biomaterial-activated macrophages – implications forin situvascular tissue engineering

Abstract: Macrophages play a governing role in material-driven tissue regeneration. Here we show that the paracrine signals of macrophages to direct tissue regeneration and scaffold degradation are dependent on hemodynamic loads.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 69 publications
(90 reference statements)
2
46
0
Order By: Relevance
“…This effect is presumably predominantly caused by stretch rather than shear effects. Nevertheless, it is conceivable that shear-dependent activation of macrophages may become relevant in conditions of alveolar fluid accumulation when fluid will cyclically shift in and out of the alveolus resulting in considerable shear forces exerted not only on alveolar epithelial cells but also on alveolar macrophages (88,89).…”
Section: Trpv4 In Mechanosensation Of Immune Cellsmentioning
confidence: 99%
“…This effect is presumably predominantly caused by stretch rather than shear effects. Nevertheless, it is conceivable that shear-dependent activation of macrophages may become relevant in conditions of alveolar fluid accumulation when fluid will cyclically shift in and out of the alveolus resulting in considerable shear forces exerted not only on alveolar epithelial cells but also on alveolar macrophages (88,89).…”
Section: Trpv4 In Mechanosensation Of Immune Cellsmentioning
confidence: 99%
“…Based on our previous study, we expected that the contribution of macrophages via direct mechanosensing would lead to increased levels of these cytokines in the presence of hemodynamic loading, especially when both loads are combined. [ 18 ] The discrepancy we find for MCP‐1 and IL‐6 indicate that (myo)fibroblasts and juxtacrine interactions between both cell types must have contributed to these secretion profiles as well. This finding corroborates with previous studies that showed that moderate stretches can promote an anti‐inflammatory environment, both via direct mechanosensing and via indirect paracrine signaling.…”
Section: Resultsmentioning
confidence: 77%
“…Previously, we showed that macrophages can also stain positive for KI67. [ 18 ] The macrophages, which we obtained from human peripheral blood mononuclear cells (hPBMCs, i.e., the CD45‐positive cells in Figure 2F), were, however, not expected to proliferate in our in vitro setup. This seemingly contrasting result is attributable to the use of a primary cell source rather than a cell line.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this could indicate enhanced oxidative and enzymatic degradative capacity of the macrophages with OSS, a previous study showed that the expression of these genes could not explain the differences in macrophage-driven scaffold mass loss, making it difficult to directly relate gene expression to scaffold degradation [31,32]. In the future, the analysis should therefore be extended with, for example, Raman spectroscopy on cross-sections, allowing the assessment of scaffold degradation across the thickness of the constructs [33].…”
Section: Results and Discussion (2397 Words)mentioning
confidence: 99%